Determinan Penerimaan Sisa Hasil Usaha Koperasi Mina Saroyo Cilacap - Riyani Agustina; Nurul Anwar; Arif Andri Wibowo (Lingka Ekonomika, 2025)
This research aims to analyze the effect of savings amount, credit, and member participation on the distribution of the cooperative's Net Income (SHU) among its members, with a case study on the Tegalkatilayu Group of the Village Unit Cooperative (KUD) Mino Saroyo in Cilacap Subdistrict, South Cilacap District. Cooperatives, particularly KUDs, play an important role in empowering rural communities, although their contribution to the national economy remains relatively low. This research used a simple random sampling method with a sample of 99 cooperative members who work as fishermen. Data was collected through interviews and analyzed using multiple linear regression. The results show that savings, credit, and member participation have a positive influence on SHU received by cooperative members. Among these variables, the savings amount is the most dominant factor affecting the SHU received. These findings indicate that the greater the members’ contributions and involvement in cooperative activities, the greater the financial benefits they receive. Therefore, active involvement of cooperative management is needed to encourage member participation so that the cooperative can grow and provide optimal economic benefits to its members.